Using the Indicator ‘Economiic Level of Technology’ in Managing Industrial and Technological Systems in Consumer Goods Industry - D. V. Khrulkov (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
The article studies issues of assessing efficiency of production and technological systems (enterprises) in consumer goods industry. Sanction restrictions built new challenges for customer goods industry but at the same time opened new opportunities. The drawback of the current approaches to managing enterprises of customer goods industry is the absence of dynamic appraisal of the technological process quality, which can cause a delayed response to crisis phenomena. To provide efficient management it is proposed to use the indicator ‘economic level of technology’ (ELT) that implies complex assessment of quality and efficiency of the production and technological system. Advantages of this indicator include possibility to forecast the development of production on the basis of due regard to laws of technological process development. With the help of calculations illustrated by two enterprises of microlevel, i.e. the transnational company Nike and the Russian company Dochki Synochki, as well as the US macroeconomic system it was proved that this indicator of efficiency can forecast arising of crucial trends in operational work of the enterprise and economy in general. Taking into account problems facing enterprises of customer goods industry ELT indicator could be used to raise effectiveness of managerial decision-making on the enterprise level and industry and state level in view of target support of development.